2021
DOI: 10.1001/jamanetworkopen.2020.36142
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Psychophysical Sequelae Among Patients With COVID-19 Four Months After Hospital Discharge

Abstract: Key Points Question What respiratory, functional, and psychological sequalae are associated with recovery from coronavirus disease 2019 (COVID-19)? Findings In this cohort study of 238 patients with COVID-19 hospitalized in an academic hospital in Northern Italy, more than half of participants had a significant reduction of diffusing lung capacity for carbon monoxide or measurable functional impairment and approximately one-fifth of patients had symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
387
7
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(489 citation statements)
references
References 41 publications
22
387
7
19
Order By: Relevance
“…[2130] Yet, only few studies have assessed the persistence of symptoms beyond three months of follow-up. [5,6,9]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2130] Yet, only few studies have assessed the persistence of symptoms beyond three months of follow-up. [5,6,9]…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort of 238 patients who suffered from severe COVID-19 requiring hospitalisation also found a higher prevalence (50%) of persistent symptoms four months after hospital discharge compared to our study. [6] Logue et al presented data from a longitudinal cohort of 177 infected individuals, which included 91% of participants with asymptomatic or mild disease. [9] They reported that 33% of outpatients and 31% of hospitalized patients reported persistent symptoms, with fatigue (14%) and loss of taste or smell (14%) being the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small cohort of critically ill COVID-19 patients also showed alteration in the diffusing capacity of the lung for carbon monoxide (D LCO ) for up to 3 months (20,27,38,40). Persistent D LCO impairment was also detected in non-critical COVID-19 patients that also presented shortness of breath and dyspnea up to 4 months after infection (18,22,33,43). Unlike the above cited studies which analyzed exclusively critically ill patients and two case-reports that analyzed solely mild COVID-19 patients (30,42) all other studies analyzed heterogeneous cohorts of patients, i.e., from mild to severe.…”
Section: Persistent Lung Symptoms and Dysfunctionsmentioning
confidence: 99%
“…It should be noted that the quality of the studies from which the information is extracted is low, and so is the power of the conclusions (mostly cohort studies, in some of which, the main objective was not the nature of symptoms, and in which the method of recruitment was variable, including self-selection surveys (high risk of bias)). There are few prospective studies with assessments beyond 12 weeks [31,[35][36][37][38][39] fulfilling the NHS current criteria for post-COVID-19 syndrome. [40][41][42][43][44][45][46][47][48][49][50] or outpatients [51][52][53][54][55][56], evaluated between 4 and 12 weeks after diagnosis.…”
Section: Clinical Manifestations Of Post-covid-19 Syndromementioning
confidence: 99%